Optimal Fiscal and Monetary Policy, Debt Crisis and Management - Cantore, Cristiano (IMF Working Papers; Working Paper, 2017)
The initial government debt-to-GDP ratio and the government's commitment play a pivotal role in determining the welfare-optimal speed of fiscal consolidation in the management of a debt crisis. Under commitment, for low or moderate initial government debt-to-GPD ratios, the optimal consolidation is very slow. A faster pace is optimal when the economy starts from a high level of public debt implying high sovereign risk premia, unless these are suppressed via a bailout by official creditors. Under discretion, the cost of not being able to commit is reflected into a quick consolidation of government debt. Simple monetary-fiscal rules with passive fiscal policy, designed for an environment with 'normal shocks', perform reasonably well in mimicking the Ramsey-optimal response to one-off government debt shocks. When the government can issue also long-term bonds-under commitment-the optimal debt consolidation pace is slower than in the case of short-term bonds only, and entails an increase in the ratio between long and short-term bonds.